Microencapsulation of linseed oil by spray drying for functional food application - Gallardo, Gabriela (2013)
Health benefits associated to ω-3 fatty acids consumption together with the high susceptibility to oxidation of ω-3 containing oils have led to the development of microencapsulated oils for nutraceutical and food enrichment applications. The aim of this work is to obtain different formulations for linseed oil microencapsulation by spray-drying with high encapsulation efficiency and evaluate their resistance to oxidation through the accelerated Rancimat test. Four formulations were tested; using different combinations of gum arabic (GA), maltodextrin (MD), methyl cellulose (MC) and whey protein isolate (WPI). Microcapsules made of 100% GA and ternary mixtures of GA, MD and WPI presented the highest protection from oxidation and microencapsulation efficiencies higher than 90%. They also presented spherical structures with smooth surfaces which kept unaltered after 10-month storage. GA containing formulation was included in bread manufacturing. Fortified bread resulted similar in appearance to control bread without microcapsules, but α-linolenic acid content was reduced significantly after preparation.